(untitled) (The Review of Diabetic Studies, 2025)
Healthcare inequalities persist across Saudi Arabia, especially among disadvantaged groups. Addressing inequities requires interdisciplinary teams to ensure equitable medical services. This study adopts a qualitative approach to analyze how collaborative models, including multidisciplinary team-based care, improve access, diagnostic accuracy, and patient-centered care. The research focuses on integrated team practices involving shared decision-making, public participation, and technology to identify mechanisms for reducing service inequities. Additionally, the study reviews the challenges of resource constraints, organizational issues, and cultural differences, and assesses strategies for fostering professional collaboration to support an inclusive health system aligned with Vision 2030.